Hospitalization for leprosy and its sequelates in the I Regional Health Management of the state of Pernambuco: Hospitalization for leprosy and its sequelates - Lima Filho, Carlos Antonio de; Alves, Silvia Maria de Luna; Coêlho, Lucas Alcindo do Nascimento; Wanderley, Flávio de Araújo; Lira, Eduardo Côrte-Real; Gouveia, Viviane de Araújo; Lira, Maria da Conceição Cavalcanti de (Journal of Health Care, 2025)
Introduction: Leprosy is an infectious, chronic and slowly evolving disease, caused by the bacterium Mycobacterium leprae. Leprosy treatment is predominantly carried out on an outpatient basis in Primary Health Care. Cases of hospitalization indicate failures of the health system in its control. Objective: To describe hospitalizations for leprosy and leprosy sequelae in residents of municipalities of I Geres in the state of Pernambuco, from 2017 to 2023. Materials and Methods: Descriptive, ecological, retrospective and epidemiological research, quantitative in nature. Hospitalizations for leprosy and its sequelae in residents of municipalities in the First Geres of Pernambuco, reported in the Hospital Information System, were included. Results: There were 1,045 hospitalizations, 76.1% in residents of municipalities in the I microregion, mainly Recife (41.9%) and Olinda (15.9%). Predominant in men (74.6%), mixed race (54.3%), between 30 and 39 years old (22.7%). Of the consultations, 75.0% were elective, with an ignored regime (100%) at Hospital da Mirueira (64.1%), with an average of 11 days. There was an expenditure of R$582,957.83, with an average of R$557.85 (0.4SM). Conclusion: Despite the low morbidity and cost, these hospitalizations proved to be a challenge for the local health system.
Keywords: Leprosy; Hospitalization; Public health; Hospital Information Systems